Incorporating culture and textbook adaptation practice for promoting intercultural competence in ELT: Teachers’ perspectives - Novita, Dian; Purwati, Oikurema (JEES (Journal of English Educators Society), 2021)
It is currently accepted that language and culture are inseparable since culture becomes an essential aspect of learning a foreign language. In the Indonesian context, this broad understanding of the crucial role of culture in English teaching has raised challenges in different contexts for EFL teachers. The recent study focuses on Indonesian Junior High School teachers’ views on integrating culture in ELT and practices of textbook adaptation to help students build intercultural competence. Therefore, to meet these aims, a questionnaire and an open-ended question were employed to collect the data from fifteen participants teaching English at public and private schools in Indonesia. The study results reveal that Indonesian EFL teachers have positive attitudes on integrating intercultural competence in ELT. Still, some of the difficulties confronted by their implementation of textbook adaptation have been highlighted in promoting intercultural competence. This study suggests that EFL teachers in Indonesia should be provided with teacher training relating to textbooks adaptation and teaching culture. The implementation of ICT in ELT classrooms is also recommended. Finally, the redesign of the curriculum with more integrated intercultural competency materials should be taken into account. HIGHLIGHTS: The EFL teachers’ practices deal with textbook adaptation are not well implemented, although they believe that cultural competence in their teaching activities is crucial. The English curriculum should give more room for teachers in serving the students based on their needs, preferences, and skills, especially for enhancing students’ mastery on the target language.